Starvation Process Would Induce Different Bacterial Mobilities and Attachment Performances in Porous Media without and with Nutrients on Surfaces - Jianmei Qin; He, Lei; Su, Xiangyu; Wang, Shuai; Meiping Tong (Environmental Science & Technology, 2024)
The influence and mechanisms of starvation on the bacterial mobile performance in porous media with different nutrition conditions are not well understood. The present study systematically investigated the impacts of starvation on the mobility and attachment of both Gram-negative and Gram-positive strains in porous media without and with nutrients on surfaces in both simulated and real water samples. We found that regardless of strain types and water chemistries, starvation would greatly inhibit bacterial attachment onto bare porous media without nutrients yet could significantly enhance cell attachment onto porous media with nutrients on their surfaces. The mechanisms driving the opposite transport behaviors induced by starvation in porous media without and with nutrients were totally different. We found that the starvation process decreased cell motility and increased repulsive force between bacteria and porous media via decreasing cell sizes and zeta potentials, reducing EPS secretion and cell hydrophobicity, thus increasing transport/inhibiting attachment of bacteria in porous media without nutrients on sand surfaces. In contrast, through strengthening the positive chemotactic response of bacteria to nutrients, the starvation process greatly enhanced bacterial attachment onto porous media with nutrients on sand surfaces. Clearly, via modification of the nutrient conditions in porous media, the mobility/attachment performance of bacteria could be regulated.